Multilevel coding scheme based on low-density parity-check codes in DAMB - WANG Jia-qing; YU Xiao-yan; WU Le-nan (Tongxin xuebao)
A multilevel coding（MLC）scheme based on LDPC codes was investigated for digital amplitude modulation broadcasting（DAMB）system.Firstly,code rates of MLC were designed,then a multistage decoding strategy was provided based on reliability information instead of only hard decisions to subsequent decoders.We also found a set of excellent irregular LDPC codes and examined the performance of them in DAMB channels.Simulations show that this scheme is more effective than the rate compatible punctured convolutional（RCPC）coded DAMB system.